2015
DOI: 10.21273/hortsci.50.9.1375
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Regeneration System for Tamarillo (Cyphomandra betacea) via Organogenesis from Hypocotyl, Leaf, and Root Explants

Abstract: Cyphomandra betacea (Cav.) is commonly known as Tamarillo or tree tomato. This species is mainly used for its edible fruits which have a high nutritional value and contain relatively high amounts of proteins, vitamins B6, C, E, and provitamin A. The cultivation of Tamarillo in Rwanda is facing major challenges caused mainly by viral diseases such as Tamarillo mosaic virus (TaMV). These diseases are difficult to control and are transferred through ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Nicotinamide was found in the non-embryogenic calli (NEC1, NEC2 and NEC3) and in EC1. 1.04 (d) 1 All metabolites were identified as putatively annotated compounds (level 2) according to the MSI guidelines unless stated otherwise; 2 putatively identified as a member of a compound class based on spectral similarity to known compounds of a chemical class (level 3); * not included in chemometric analysis.…”
Section: Metabolite Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinamide was found in the non-embryogenic calli (NEC1, NEC2 and NEC3) and in EC1. 1.04 (d) 1 All metabolites were identified as putatively annotated compounds (level 2) according to the MSI guidelines unless stated otherwise; 2 putatively identified as a member of a compound class based on spectral similarity to known compounds of a chemical class (level 3); * not included in chemometric analysis.…”
Section: Metabolite Identificationmentioning
confidence: 99%
“…Sendt. ), is a small solanaceous tree or shrub endogenous to South America [1]. Because of its edible fruits, it is currently grown globally, namely in New Zealand, Australia and California, USA [2].…”
Section: Introductionmentioning
confidence: 99%
“…(syn. Cyphomandra betacea ) is a small (2–4 m high) solanaceous tree indigenous to South America, specifically to the Andean regions of Argentina, Bolivia Chile, Ecuador, and Peru, and currently cultivated around the globe, namely in California and New Zealand [ 1 ]. In its natural environment, tamarillo is found between 700 and 2000 m, preferring lower altitudes in colder climates [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyphomandra betacea is a fruit tree rich in proteins and vitamins with high nutritional value 24,25 . A previous study reported that the high Se concentration in the soil increased the Se content in C. betacea 26 .…”
Section: Introductionmentioning
confidence: 99%